Survey Minimasi Sampah Di Bank Sampah DLH Beringin Jaya Kota Bandar Lampung - Enro Sujito; Imam Santosa; Linda Barus; Nawan Prianto; Daria Br Ginting (CV. Multi Kreasi Media, 2023)
Waste is still a problem in the city of Bandar Lampung. Where the Environmental Service of the city of Bandar Lampung in the Beringin Jaya sub-district, Kemiling District, has succeeded in running the Garbage Bank organization since 2019. However, the Environmental Service Garbage Bank (DLH) in the Beringin Jaya sub-district, Kemiling District, Bandar Lampung City has not yet been operating optimally. One reason is that there is no data on waste minimization in Beringin Jaya Village, so that the amount of organic waste and inorganic waste produced can be calculated. The purpose of this community service activity is to find out an overview of the Beringin Jaya Environmental Service Garbage Bank and find out the amount of waste minimization in Bringin Jaya Village before it is disposed of in the TPA. The research methodology is as follows: Preparation, Implementation and Evaluation. The result of community service is that the current operation of the Bringin Jaya Village waste bank is making compost, packing the compost and the amount of waste generation in Beringin Jaya Village is 7,040 kg per day, consisting of 4,928 kg organic waste/day.